Human capital planning of universities in Ghana: A comparative analysis of the University of Cape Coast and University of Education, Winneba - Justice K.G Agyenim Boateng; Daishonin Baah-Koranteng; John Linscell Yen; Emmanuel Asafo-Adjei; Anokye M. Adam (Cogent Business & Management, 2023)
The study was conducted on universities in Ghana because of the challenges of the increase in talent shortfalls, reduction in their aptitude to forecast future talent needs and a surge in the risk of being overstaffed or understaffed, and the presence of an inappropriate mix of the skills they need to develop the human capital. It enjoins universities to develop effective human capital planning systems. However, it is yet known how universities in Ghana in particular plan their human capital requirements. Particularly, the status of the present human capital in universities in Ghana based on differences among universities for achieving the objectives of human capital planning has not been researched. Hence, the study investigated the status of human capital planning (HCP) at the University of Cape Coast (UCC) and the University of Education, Winneba (UEW), both in the Central Region of Ghana. A descriptive design and quantitative approach with a stratified sampling technique were employed for a sample of 138 senior members in both academic and non-academic fields for the study out of which 106 responded to a structured questionnaire. The Mann-Whitney U test was used as the estimation technique. We revealed that there are no significant differences between the two institutions as the emphasis placed on the various factors of the HCP process was similar in both institutions. We recommend that more concerted efforts should be made towards HCP in UCC and UEW to enhance productivity and institutional growth.
Keywords: 650; analysing; directing; monitoring; organising; planning; senior members; test of differences; university staff